To politicize or depoliticize, is that really the question of administrative adjudication?: A study of the state council judicial interpretation in Egypt - ElSammak, Abouelfetouh (AUC Knowledge Fountain, 2019)
When a court is called upon to adjudicate, it is crucial to establish the meaning of the norm, allegedly governing the litigants in order to apply it. Legal interpretation is, hence, the beating heart of judicial activism. It is an intellectual process that shows the judge's appreciation and their personal understanding of the facts and the ability to localize the court’s boundaries within the public system of the State. Legal interpretation is often used strategically to advance a certain judicial policy, which is always at the background of the judge reasoning. The court deviates from the obvious rule interpretation and adopts a certain interpretation that can only be justified by policy or practical considerations. This thesis tends to demonstrate the judicial activism in Egypt regarding the legal interpretation of the State Council judges, through the examination of different court reasoning that shows a pattern of subconscious activity related to the political analysis of the case facts. I intend to demonstrate that when the relation between the Government and the Parliament is facing turmoil or one authority is consumed by the other, the State Council is obliged to raise its jurisdiction in order to maintain the balance between public authorities and preserve the public interest by protecting individual rights and enforcing high standards of public governance. The conclusion is far from being conclusive. If legal interpretation is means to an end, with the end supposedly the public interest, then legal interpretation is no longer a reflection of the court’s understanding of law but rather how it perceives the separation of powers principle and its duty to protect the public interest, which is highly related to political and practical considerations of each case.